Nonlinear transformation of waves with different polarizations in finite-length layered superconductors - Rokhmanova, T.N.; Apostolov, S. S.; Maizelis, Z.A.; Yampolskiy, V.A. (Reports of the National Academy of Sciences of Ukraine, 2015)
We study theoretically the reflection, transmission, and mutual transformation of nonlinear TE and TM waves in the terahertz frequency range in a finite-length sample of the layered superconductor placed inside a waveguide. The superconducting layers are considered to be parallel to the waveguide axis. It is shown that there exist waves of two mutually orthogonal polarizations that reflect and transmit independently of each other despite a nonlinearity. Thus, the superposition principle is formulated for these waves, which can be used for solving the nonlinear problems of interactions of waves in layered superconductors.